The effect of physical training on the general endurance and fitness of "Beladi" club for advanced football player’s - Najeeb Asleawa, Wesam; Kadhim Ali , Naji; Sami Yousif Malik, Faris (International Journal of Psychosocial Rehabilitation, 2020)
The proper planning and selection of appropriate exercises enables the trainer to develop physical characteristics and at the same time works to master the player's basic skills and digest play plans. It has been proven that the football player needs in many situations to have the necessary agility, swaying and changing directions, shifting play and various central reactions such as preparing the ball and spinning or avoiding collision with the opponent's body or avoiding obstruction as well as speed of standing from falling on the ground and avoiding injuries and achieving the best achievement. The study proved that endurance is indispensable because it is through which the player can perform an activity in difficult play with high intensity for a long time and maintain this activity without falling in the effectiveness of skills and planning capabilities. It has been proven that the trait of endurance has a close correlation with both strength and speed in order to develop both (bearing strength - bearing speed).